Pengaruh Serat Selulosa Asetat Filter Rokok Terhadap Karakteristik Marshall Campuran AC-WC - Muhammad Aminsyah (Universitas Andalas, 2025)
The increase in traffic in Indonesia is in the form of increasing volume and weight of vehicles. Good road construction quality is needed, namely high stability. Additives in asphalt mixtures are used to improve the quality of the mixture. One form of additive that can be used is cellulose fiber found in cigarette filters. Cigarette filters produce waste that has an impact on the environment. This study aims to determine the effect of cellulose acetate fiber from cigarette filters and its optimum content in the AC-WC (Asphalt Concrete Wearing Coarse) mixture. The Marshall method was used in this study. Cigarette filter waste of 3%, 5%, 7%, and 9% was added to the asphalt. The results of the study were an optimal percentage of cigarette filter waste of 7%, with a stability value of 2804.14 kg and an MQ value of 477.26 kg / mm. The addition of cigarette filters to asphalt resulted in an increase in the specific gravity value and a decrease in the asphalt penetration value.